2023
DOI: 10.1002/jia2.26052
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of broadly neutralizing antibody prophylaxis for HIV‐exposed infants in sub‐Saharan African settings

Abstract: Introduction Infant HIV prophylaxis with broadly neutralizing anti‐HIV antibodies (bNAbs) could provide long‐acting protection against vertical transmission. We sought to estimate the potential clinical impact and cost‐effectiveness of hypothetical bNAb prophylaxis programmes for children known to be HIV exposed at birth in three sub‐Saharan African settings. Methods We conducted a cost‐effectiveness analysis using the CEPAC‐Pediatric model, simulating cohorts of infants from birth through death in Côte d'Ivoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Currently, bNAbs are not commercially available, making the production cost study-specific and expensive. One cost-effectiveness study has been performed evaluating bNAbs for PVT [43], but to the best of our knowledge, no study to date has evaluated the cost-effectiveness of strategies involving bNAbs as a treatment strategy. As more potent and broader-acting agents become available, and potential agents with longer half-lives, feasibility considerations will continue to evolve for the field as a whole.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Currently, bNAbs are not commercially available, making the production cost study-specific and expensive. One cost-effectiveness study has been performed evaluating bNAbs for PVT [43], but to the best of our knowledge, no study to date has evaluated the cost-effectiveness of strategies involving bNAbs as a treatment strategy. As more potent and broader-acting agents become available, and potential agents with longer half-lives, feasibility considerations will continue to evolve for the field as a whole.…”
Section: Future Considerationsmentioning
confidence: 99%
“…However, there are use case examples for how these evaluations are leveraged for internal decision making ( 2 , 23 ) and to mitigate the risks ( 23 ) and high costs of late-stage development ( 23 ). In this context, they can provide valuable insights into clinical trial design ( 23 , 24 ), into target populations or other drivers that improve value for money ( 25 , 26 ) and can guide decisions on what data need to be collected at the next phase of development ( 27 ) so that uncertainty is reduced when introduction decisions are made by policy makers and payers. Importantly, these early analyses can inform product developers' decisions on how to improve a product's eventual value for money, helping refine the target product profile as well as informing which product to prioritise across a given portfolio, focusing resources on those most promising products for further development and those most appropriate for a future programme ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Linked model outputs include estimates of efficacy, dosing regimen, pharmacokinetics, among others. These outputs can guide clinical development and help reframe value propositions once new data are collected during the different stages of clinical trials, providing an iterative framework for decision making ( 35 , 36 ), future trial design ( 25 ), and the preparation of strategies for reimbursement and pricing ( 2 , 29 , 32 , 37 39 ). Though researchers often emphasize the uncertainty that comes with modelling early in the development process as a limitation of early economic modelling ( 2 , 22 24 , 28 32 ), the framing and communication of this uncertainty becomes the objective of these analyses and future evidence generation will revolve around addressing this uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous modeling work found that offering a bNAb to infants with known HIV exposure at birth would be cost-effective in Côte d’Ivoire, South Africa, and Zimbabwe. 11 However, the potential long-term, population-level clinical benefits and cost-effectiveness of a universal infant bNAb prophylaxis program in high HIV burden settings have not yet been studied. Here, we extend our prior modeling work to include infants born to mothers with unrecognized HIV infection or mothers at risk for acute HIV acquisition postpartum.…”
Section: Introductionmentioning
confidence: 99%